Investigating the role of allergic contact dermatitis in residual ocular surface disease on dupilumab (ROSDD) - Jodie Raffi, BA; Raagini Suresh, BS; Harvey Fishman, MD, PhD; Nina Botto, MD; Jenny E. Murase, MD (Wolters Kluwer, 2019)
Background: The mechanisms underlying eye-related complications with dupilumab are poorly understood. Objective: This study aimed to determine the incidence and characteristics of ocular complications with dupilumab and the prevalence of comorbid allergic contact dermatitis in the same subpopulation. Methods: This is a retrospective chart review of 48 patients with atopic dermatitis who received dupilumab. For patients with eye involvement at first follow-up, we discuss the presence of eyelid dermatitis, blepharitis, or conjunctivitis and analyze available patch test findings in patients with ocular complications while treated with dupilumab. Results: A total of 14 patients (29.2%) showed eye involvement while on dupilumab, all of whom experienced eye involvement prior to dupilumab. The results of the patch test were most commonly positive for emulsifier/surfactants (42.5%) and fragrances (30.4%). Nine patients experienced improvement with allergen avoidance subsequent to patch testing, and four of nine patients' conditions cleared almost entirely. This is a non-randomized study in a small cohort of patients. Only 18 patients had their disease confirmed by an ophthalmologist. Conclusion: All patients with eye involvement while on dupilumab had a history of eye involvement prior to dupilumab, suggest that dupilumab may encourage rather than cause ocular surface inflammation. Significant improvement after patch testing in nearly half of patients suggests that allergic contact dermatitis contributes to some cases of dupilumab-associated eye complications. Keywords: Atopic dermatitis, Allergic contact dermatitis, Dupilumab, Patch testing, Conjunctivitis, Blepharitis